A circus wish - Bentley, Sue, 1951-; Swan, Angela (New York : Grosset & Dunlap, 2009)
A magic kitten helps Sadie and her best friend Jenny overcome their differences and find a way to enjoy performing in the circus together.
4-8
Accelerated Reader AR
Keywords: Circus -- Fiction; Cats -- Fiction; Magic -- Fiction; Friendship -- Fiction